2022
DOI: 10.1002/ehf2.14083
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine hormone status and diuretic response to atrial natriuretic peptide in patients with acute heart failure

Abstract: Aims Given the various effects of sacubitril/valsartan in heart failure, a deeper understanding of atrial natriuretic peptide (ANP) actions is warranted. Natriuresis is a fundamental action of ANP in acute heart failure (AHF), whereas the diuretic effect of ANP is different in each patient according to the diversity of renal response to ANP, which is affected by baseline plasma ANP status and deficiency of circulating ANP. Meanwhile, associations between other neuroendocrine hormones and the diuretic response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Current research has confirmed that ARNI can inhibit neuroendocrine over-activation, exerting favorable sodium excretion, vasodilatation, diuresis, etc., thus promoting the improvement of the condition of heart failure. 43 , 44 ARNI has now become a category of recommendation for the treatment of patients with heart failure. The purpose of this trial is to clarify whether RDN is equally effective in improving cardiac function by comparing RDN with ARNI.…”
Section: Discussionmentioning
confidence: 99%
“…Current research has confirmed that ARNI can inhibit neuroendocrine over-activation, exerting favorable sodium excretion, vasodilatation, diuresis, etc., thus promoting the improvement of the condition of heart failure. 43 , 44 ARNI has now become a category of recommendation for the treatment of patients with heart failure. The purpose of this trial is to clarify whether RDN is equally effective in improving cardiac function by comparing RDN with ARNI.…”
Section: Discussionmentioning
confidence: 99%
“…60 Management of HF aims at addressing both hemodynamic compromise and reperfusion to restore myocardial contractile function. [61][62][63] Although the HF market has numerous well-established therapies and the pipeline is promising, there is a considerable level of unmet needs.…”
Section: Nanotechnology and Heart Failurementioning
confidence: 99%
“…This is probably why the more advanced HF patients (patients who take diuretics for longer periods of time) need higher doses of the drugs 8 . The diuretic response is also highly related to the neurohormonal drive, which can also identify patients with more disrupted pathophysiology and worse outcomes 9–11 . Several studies have demonstrated the association between the dose of diuretics and the outcomes, but this has never been demonstrated in a casual‐effect manner as most of the data come from retrospective analyses or registries 12,13 .…”
mentioning
confidence: 99%
“… 8 The diuretic response is also highly related to the neurohormonal drive, which can also identify patients with more disrupted pathophysiology and worse outcomes. 9 , 10 , 11 Several studies have demonstrated the association between the dose of diuretics and the outcomes, but this has never been demonstrated in a casual‐effect manner as most of the data come from retrospective analyses or registries. 12 , 13 Unfortunately, at the moment, we lack objective measures that allow us to adjust the loop diuretic doses in HF patients.…”
mentioning
confidence: 99%